Changes in the diversity of ginseng endophyte flora driven by Fusarium solani - Zhuo Sun; Zhuo Sun; Yang Hu; Yi-Xin Yang; Meng-Yuan Lei; Zhong-Ming Han; Lin Cheng; Wan Wang; Mei Han; Ze-Liang Lyu; Li-Min Yang (Frontiers in Microbiology)
Endophytic flora serves a crucial function as a secondary line of defense against pathogen invasion in plants. To investigate the mechanisms underlying the relationship between changes in endophytic flora and ginseng root rot, exhumate beneficial endophytic bacteria, and explore biological management approaches for ginseng root rot. In this study, we used Illumina high-throughput sequencing and bioinformatics analysis to investigate the characteristics and differences in endophytic microbial community structure between healthy ginseng (HG) and diseased ginseng (BLS) after Fusarium solani infection. The findings revealed that as ginseng root rot increased, the diversity and richness of endophytic bacterial communities increased before decreasing, but the diversity and richness of endophytic fungal communities decreased. The dominating bacterial phylum in ginseng roots was Proteobacteria, which declined in quantity as the disease progressed. Ascomycota was the dominating fungal phylum among endophytes, and its prevalence grew as the disease progressed. At the genus level, the relative abundance of Rhodococcus, Stenotrophomonas, Variovorax, and Achromobacter species increased with the occurrence of ginseng root rot, in contrast, Pantoea and Pseudomonas species decreased in relative abundance as the prevalence of ginseng root rot increased. The relative abundance of the pathogenic fungi Gibberella, Nectria, Ilyonectria, and Alternaria in ginseng roots increased as the disease progressed. Endophytic fungal LEfSe research revealed that Neonectria was the particular biomarker discovered in the highly susceptible group. Additionally, commensal nutrient-type fungi appeared to be absent in moderately susceptible ginseng, but pathognomic nutrient-type fungi grew, coupled with potentially pathogenic fungi, exacerbating the condition. These results suggest that there is a pattern of response of ginseng endophytic microbial diversity to disease infestation. In this work, we investigated the impact of varying degrees of root rot on ginseng’s endophytic flora structure. The study’s findings give a theoretical framework for understanding the microecological processes of ginseng root rot via the lens of microbial ecology and applying biological control tools.